ROLE OF CYTOKINES IN THE DEVELOPMENT OF LIVER CIRRHOSIS, WHICH DEVELOPED AS A RESULT OF CHRONIC VIRAL HEPATITIS D (REVIEW ARTICLE) - Abdurashid R. Obloqulov; Aziza A. Elmurodova; Donohon N. Achilova (Central Asian Journal of Medicine, 2023)
Hepatitis D is an inflammation of the liver caused by the hepatitis D virus (HDV), which requires HBV for its replication. Hepatitis D infection cannot occur in the absence of hepatitis B virus. HDV-HBV co-infection is considered the most severe form of chronic viral hepatitis due to more rapid progression towards hepatocellular carcinoma and liver-related death.